2019
DOI: 10.32770/rbaos.vol1129-140
|View full text |Cite
|
Sign up to set email alerts
|

Work Placement, Organizational Commitment and Employee Performance:

Abstract: Mismatch between skills, expertise and work placements among civil servants is often a phenomenon that occurs in many public service offices in Indonesia. This condition is exacerbated by low organizational commitment. Because these two aspects can lead to poor public service, this study aims to evaluate the impact of work placements and organizational commitment on employee performance. The results of Partial Least Square (PLS) analysis show that work placements have a positive and significant impact on emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
1
3
2
1
Order By: Relevance
“…This result is in contrast with that of Sari and Sa'adah (2019) which found that work placement of teachers has a favourable and important impact on their job results. However, despite its positive effect on workers' execution of tasks, employee commitment does not significantly affect their performance (Khaerudin et al, 2018;Sari & Sa'adah, 2019); implying that a committed employee can perform poorly on the job and vice versa. The various roles and strategies that are essential to advance educators' success are unknown to school leaders (Hashmi, 2014).…”
Section: Staff Placement and Educators' Job Commitmentcontrasting
confidence: 96%
See 2 more Smart Citations
“…This result is in contrast with that of Sari and Sa'adah (2019) which found that work placement of teachers has a favourable and important impact on their job results. However, despite its positive effect on workers' execution of tasks, employee commitment does not significantly affect their performance (Khaerudin et al, 2018;Sari & Sa'adah, 2019); implying that a committed employee can perform poorly on the job and vice versa. The various roles and strategies that are essential to advance educators' success are unknown to school leaders (Hashmi, 2014).…”
Section: Staff Placement and Educators' Job Commitmentcontrasting
confidence: 96%
“…An exploratory study of 50 respondents using a purposive sampling approach revealed, first, that there is no association between school administration and recently gathered knowledge and abilities of human resource managers (Hashmi, 2014). This result is in contrast with that of Sari and Sa'adah (2019) which found that work placement of teachers has a favourable and important impact on their job results. However, despite its positive effect on workers' execution of tasks, employee commitment does not significantly affect their performance (Khaerudin et al, 2018;Sari & Sa'adah, 2019); implying that a committed employee can perform poorly on the job and vice versa.…”
Section: Staff Placement and Educators' Job Commitmentmentioning
confidence: 91%
See 1 more Smart Citation
“…This finding contrasts with another study which discovered that teachers' work placement positively influenced their employment outcomes ( Sari & Sa'adah, 2019 ). Similarly, it has been argued that employee commitment positively impacts workers' task performance but not their overall quality of work ( Khaerudin et al., 2018 ).…”
Section: Review Of Related Literature and Theoretical Frameworkcontrasting
confidence: 98%
“…Özgenel andKarsantik (2020) noted that comparing married and unmarried principals, some significant differences and interesting similarities in the type and amount of support provided to married and unmarried principals have been chronicled thus far. Sari and Sa'adah (2019) posited that work placements and organizational commitment specifically recognizing various appointments played vital role on employee performance. Further, monthly income had been scattered in various groupings of salary range.…”
Section: Discussionmentioning
confidence: 99%